Fleet Dispatches in Fourth-Century BC Athens - Gabrielsen, Vincent (Classica et Mediaevalia, 2026)
In his First Philippic, Demosthenes ranks the Athenian navy as inferior to Philip II’s Macedonian navy primarily because of its unpreparedness and dilatory fleet dispatch procedures. In accord with this assessment, a recent paper makes particularly the quarrels and lawsuits between trierarchs the causes of delayed expeditions and the poor performance of the Athenian navy in the fourth century. The present paper scrutinizes both of these claims. It concludes that a larger body of evidence contradicts Demosthenes’ assessment and shows the claims of the recent paper to lack empirical support.